S129 Decreased cAMP Production in Lung Fibroblasts from Patients with Idiopathic Pulmonary Fibrosis. (19th November 2012) - Simms, RL; Coward, WR; Knox, AJ; Pang, L
Abstract : Rationale: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease with unknown aetiology and no effective therapy. Myofibroblasts are the primary effector cells in the pathogenesis of IPF and differentiation from fibroblasts is a major source of myofibroblasts. Prostaglandin E2 (PGE2 ) inhibits fibroblast to myofibroblast differentiation via the E Prostanoid 2 (EP2) receptor and cAMP, suggesting cAMP is a key regulator of myofibroblast differentiation. The aim of the present study was to evaluate the effect of different cAMP elevating agents on myofibroblast differentiation. Methods: Fibroblasts from lungs of patients with IPF (F-IPF) and from non-fibrotic lungs (F-NL) were used. TGF-β1 (2ng/ml 3d) was used to induce myofibroblast differentiation. The effect of PGE2, β2-agonists Salmeterol and Formoterol, the direct adenylyl cyclase activator Forskolin and the phosphodiesterase 4 (PDE4) inhibitor Roflumilast (all 1µm, 3d) was evaluated. IL-1β (2ng/ml, 24hr) was used for cyclooxygenase 2 (COX-2) induction. α-smooth muscle actin (α-SMA, a myofibroblast marker), COX-2, EP2, EP4 and β2-receptor expression was analysed by Western blotting and immunocytochemistry, respectively. Adenylyl cyclase mRNA was measured by qPCR and cAMP was measured by radioimmunoassay. Results: F-IPF showed increased α-SMA and collagen expression and repressed COX-2 expression compared to F-NL. PGE2 treatment prevented TGF-β1-induced α-SMA expression and COX-2 repression in F-NL, which was mimicked by β2-agonists and Forskolin. PGE2 also reduced α-SMA expression and increased COX-2 expression in F-IPF despite that it induced significantly less cAMP than in F-NL But this effect on F-IPF was not mimicked by β2-agonists and Forskolin as they induced even less cAMP than PGE2 in these cells. TGF-β-treated F-NL also produced less cAMP than untreated cells in response to these cAMP. stimulants. However, the expression of EP2, EP4, β2-adrenoceptors and adenylyl cyclase isoforms was similar in F-NL and F-IPF. Furthermore, combination of PGE2 with Roflumilast showed greater effect than PGE2 alone on α-SMA reduction and COX-2 expression in F-IPF and F-NL, whereas Roflumilast alone had no effect. Conclusions: cAMP is a key anti-fibrotic regulator of myofibroblast differentiation. However, cAMP production in myofibroblasts is defective, probably due to increased degradation by PDE4.